2012
DOI: 10.2147/clep.s28410
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal disease: changes in epidemiology and prevention

Abstract: The human bacterial pathogen Neisseria meningitidis remains a serious worldwide health threat, but progress is being made toward the control of meningococcal infections. This review summarizes current knowledge of the global epidemiology and the pathophysiology of meningococcal disease, as well as recent advances in prevention by new vaccines. Meningococcal disease patterns and incidence can vary dramatically, both geographically and over time in populations, influenced by differences in invasive meningococcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 97 publications
0
58
0
3
Order By: Relevance
“…In 2006, with the extensive use and implementation of the MenC conjugate vaccine, the epidemiological situation changed again, making MenB the principal agent of meningitis and septicemia, mainly affecting children in the first months of life and adolescents. 1,20 The molecular epidemiology studies have confirmed that several hundred PorA genotypes have been identified among capsular group B isolates worldwide. Anyway, even if the disease is caused by relatively few PorA subtypes, the development of a PorA based vaccine against MenB has been hampered by the requirement to obtain a broad protection against heterologous strains (PorA subtypes).…”
Section: Epidemiologymentioning
confidence: 95%
“…In 2006, with the extensive use and implementation of the MenC conjugate vaccine, the epidemiological situation changed again, making MenB the principal agent of meningitis and septicemia, mainly affecting children in the first months of life and adolescents. 1,20 The molecular epidemiology studies have confirmed that several hundred PorA genotypes have been identified among capsular group B isolates worldwide. Anyway, even if the disease is caused by relatively few PorA subtypes, the development of a PorA based vaccine against MenB has been hampered by the requirement to obtain a broad protection against heterologous strains (PorA subtypes).…”
Section: Epidemiologymentioning
confidence: 95%
“…Per quanto concerne la sintomatologia va sottolineato che, trattandosi di un bambino, a volte i sintomi classici possono non essere presenti o comparire in maniera atipica: infatti la temperatura corporea ha manifestato, durante l'osservazione ospedaliera, solo tre accessi (in due giornate) su un andamento pressoché costantemente afebbrile, prevalendo così, nel nostro caso, la sintomatologia da irritazione meningea. Dal punto di vista epidemiologico il sierogruppo W riscontrato ci permette di focalizzare l'attenzione su un dato fondamentale: la variabilità delle caratteristiche sierotipiche e dell'incidenza della malattia da meningococco, sia geograficamente sia nel corso del tempo [7]. Infatti, sia in Europa sia, in scala più ampia, a livello mondiale, emergono casi singoli o focolai attribuibili a sierogruppi diversi da quelli endemici, considerati propri di una determinata area geografica.…”
Section: Caso Clinicounclassified
“…Qui la malattia è endemica e l'80-85% dei casi riscontrati sono da attribuire al meningococco di sierogruppo A [5], anche se ultimamente vengono segnalate variazioni di tendenza [7].…”
Section: Introduzioneunclassified
See 1 more Smart Citation
“…It usually exists in an asymptomatic nasopharyngeal carriage state at a rate of 0.4% to 25% in human populations (1,2). However, N. meningitidis can cause devastating invasive diseases, such as septicemia or meningitis, by penetration of the mucosal tissue, invasion of the bloodstream, and colonization of the meninges.…”
mentioning
confidence: 99%